Nascent Malunion of an Isolated Intraarticular Fracture of the Ulnar Head - Nienstedt, Frank; Mariacher, Markus; Stuflesser, Günther; Berger, Wilhelm (Journal of Wrist Surgery, 2020)
Background Isolated fractures of the ulnar head are rare. Only few cases have been reported in literature.Case Description We report a case of a 16-year-old student who was treated for an ulnar styloid fracture conservatively. An associated displaced intraarticular fracture of the ulnar head has been overlooked. He presented late in our clinic with a symptomatic nascent malunion of the ulnar head fracture. A corrective osteotomy by a palmar approach was performed. Fixation by screws was used with an excellent result at 7-year follow-up.Literature Review The rare cases of isolated ulnar head fractures reported in literature were treated by open reduction and internal fixation only in case of fracture dislocation.Clinical Relevance The authors highlight the fact that even a nascent malunion of an isolated intraarticular fracture of the ulnar head may be treated successfully by open reduction and internal fixation.
Keywords: ulnar head fracture; nascent malunion; osteotomy